Dissecting the role of KLF5: from tumor progression to immune interactions with emphasis on glioma and bladder cancer - Yuan, Ze; Situ, Minyi; Ye, Yimeng; Zhang, Jinhui; Jiang, Kuntai; Zhang, Shingyik; Deng, Xinpei; He, Zhenqiang; Luo, Juncheng; Wang, Yanjun (Frontiers in Immunology, 2026)
BackgroundKrüppel-like factor 5 (KLF5) is involved in various aspects of tumor development, metastasis, and drug resistance through their regulation of transcription and translation, yet its functions in a comprehensive cancer framework are still unclear.MethodsOur research involved a detailed pan-cancer analysis using multi-omics data sourced from various public databases. We investigated the clinical characteristics, prognostic significance, mutations, and methylation patterns of KLF5 across various cancer types.ResultsWe discovered that KLF5 is implicated in tumor progression and are prognostic markers across pan-cancer. KLF5 is significantly linked to various malignant pathways across different types of cancer. Additionally, KLF5 has associations with several immune-related features. Ultimately, experiments were carried out to investigate whether KLF5 could serve as a promising indicator for glioma and bladder cancer.ConclusionKLF5 may be utilized as a diagnostic tool for cancer, a predictor of its progression, and a guide for treatment., with particular promise as a therapeutic target for glioma and bladder cancer.